2007
DOI: 10.1111/j.1439-0396.2007.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective rumen degradation of dry matter, crude protein and neutral detergent fibre in forage determined by near infrared reflectance spectroscopy

Abstract: The objective of the present study was to examine if near infrared reflectance spectroscopy (NIRS) could be used to predict degradation parameters and effective degradation from scans of original forage samples. Degradability of dry matter (DM), crude protein (CP) and neutral detergent fibre (NDF) of 61 samples of perennial ryegrass (Lolium perenne L.) and orchardgrass (Dactylis glomerata L.) was tested by using the in situ technique. The grass samples were harvested at three different stages, early vegetative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
6
19
0
1
Order By: Relevance
“…Several studies reported the inability of NIRS to predict the rate of degradation of nutrients (Andrés et al, 2005b;Nordheim et al, 2007;Ohlsson et al, 2007). Herrero et al (1997) related this difficulty to the exponential nature of the models used in parameterization of the degradation rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported the inability of NIRS to predict the rate of degradation of nutrients (Andrés et al, 2005b;Nordheim et al, 2007;Ohlsson et al, 2007). Herrero et al (1997) related this difficulty to the exponential nature of the models used in parameterization of the degradation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Belanche et al (2013 and2014) used Fourier transformation mid-IR spectroscopy (FTIR) to estimate degradability parameters of CP, dry matter (DM) and NDF, and results suggested that mid-IR can be used for screening purposes but not for estimating dynamic parameters of degradability. Similarly, several efforts using NIRS to predict rumen degradation parameters have been reported (Todorov et al, 1994;De Boever et al, 2003;Andrés et al, 2005b;Ohlsson et al, 2007). However, most of these studies are feedstuff specific, predicting degradation parameters of a particular feedstuff or a specific category of feedstuffs, mainly forages or compound feeds and not byproducts or grains.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] Methods employing IR spectroscopy have been successfully used to determine nutrient contents of milk, 36,37 colostrum IgG concentration, 33 feed composition, and the kinetics of nutrient degradation in the rumen. 20,31 It has also been utilized in screening for metabolic diseases such as ketosis 18 and foodborne pathogens. 7 However, there are a number of IR spectroscopic sampling techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods are robust and can be applied to a wide variety of feeds, some limitations have been observed. This type of analysis provides chemical-structural information about the feed, allowing the chemical composition of and the kinetic processes that degrade ruminal food to be inferred (Andrés et al, 2005;Ohlsson et al, 2007). The FTIR technique has recently been developed; it is more sensitive than traditional methods, and data can be obtained more quickly (Belanche et al, 2013).…”
Section: Methodologies For Predicting Protein Degradability In the Rumenmentioning
confidence: 99%
“…Another interesting conclusion of this study was that the majority of FTIR-based predictions show a similar level of accuracy as the NIRS method, suggesting that FTIR should be considered as a low-cost alternative method for the nutritional evaluation of feeds. Although NIRS has demonstrated some capability for directly predicting the degradability of forage components in situ (Nordheim et al, 2007;Ohlsson et al, 2007), approximately 12,000 dacron bags would need to be processed for calibration purposes (Hoffman et al, 1999). Given this complexity, NIRS is proposed as a reliable technique for predicting the composition of incubation residues for which calibration requires fewer observations (Reeves et al, 1991;Berzaghi et al, 1997;Andrés et al, 2005).…”
Section: Methodologies For Predicting Protein Degradability In the Rumenmentioning
confidence: 99%